Robot-Assisted Laparoscopic Radical Prostatectomy: A Review of Technique and Outcomes - Taner Kargi; Nevzat Can Sener (European Medical Journal, 2016)
There has been an increase in the incidence of prostate cancer over time, and it now constitutes 15% of all male cancers in developed countries and 4% in developing countries. Radical prostatectomy is the gold-standard treatment choice in cases determined with organ-confined prostate cancer and life expectancy is >10 years. Currently in the USA, 80% of radical prostatectomy operations are robot-assisted. Although there is an additional financial burden in comparison with open surgery radical prostatectomy, the early recovery of functional status of continence and potency seem to be major advantages of the robotic method. However, there is clearly a need for future prospective studies of large patient series with longer follow-up to further clarify the financial issues, and the oncological and functional status.